Patterns and risks of microplastic release during primary oral care in Chinese residents - Shuai Wang; Na Zheng; Liyuan Peng; Qirui An; Changcheng Chen; Yijun Wei (Ecotoxicology and Environmental Safety, 2025)
This study characterized microplastics (MPs) generated from the toothpaste and toothbrushes commonly used in China based on a survey of oral care product usage. The study examined the time-dependent trend of MPs released from toothbrushes and evaluated the risk of microplastic exposure through oral products in a Chinese population. MPs in the toothpaste were composed of translucent and irregularly fragmented polyethylene (22 %) and polyethylene-vinyl acetate (78 %). A toothbrush simulation revealed the highest percentage of polypropylene (22 %) and the dominance of microplastic < 100 μm (63 %). The temporal trend of MPs release indicated that the release rate of MPs from hard-bristled toothbrushes increases rapidly initially and then gradually during use. The results suggest that the use of popular Chinese toothbrushes and toothpastes does not directly contribute to the health risks associated with exposure to MPs. However, daily releases were up to 11.83 × 105 particles/year/person from the toothpaste and an average of at least 23.3 × 105 particles/year/person from the toothbrush. Continuous daily use of toothpaste and toothbrushes releases large numbers of MPs into the environment.